Strategi Kepala Sekolah Dalam Mengatasi Permasalahan Pembelajaran Online di Masa Pandemi COVID 19 - Asha, Lukman (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2021)
The purpose of this research was to gain an understanding of the principal's strategies as a manager in overcoming problems that arouse during the implementation of online learning at SDIT al-Kahfi in Lebong Regency, Bengkulu Province. This study applied a qualitative approach, with data gathered through observation of learning activities via Whastapp groups and interviews with informants such as school principals, PAI teachers, students, and parents. Following the collection of data, an analysis was performed using Miles’ et al theory in order to find conclusive answers. The principal's strategies to solve the problems of online learning at SDIT al-Kahfi Lebong fell into the following: sending teachers to attend seminars or getting engaged into the training of information technology and learning with peers, providing guidance or training for children in groups or individually, providing counseling and conducting counseling meetings with students’ parents about the importance of android in the learning process, and giving an understanding of the importance of parental cooperation in supervising their children's learning from home.